Cholecystectomy-induced secondary bile acids accumulation ameliorates colitis through inhibiting monocyte/macrophage recruitment - Yun Liu; Jun Xu; Xinhua Ren; Yu Zhang; Ziliang Ke; Jianhua Zhou; Yang Wang; Yifan Zhang; Yulan Liu (Gut Microbes)
Although post-cholecystectomy (PC) patients usually have gastrointestinal complications and a higher risk of colorectal cancer, previous studies undetected a heightened risk of inflammatory bowel disease. Thus, we tried to investigate cholecystectomy’s impact and pathophysiological mechanism on murine colitis models and clarify the association among fecal bile acids (BAs), mucosal bacterial microbiota, and immune cells in the PC patients. One month or three months after cholecystectomy, mice have induced colitis and tested BAs and fecal microbiota analysis. Next, mice were treated with various cholecystectomy-accumulated bile acids in drinking water for three months before inducing colitis. All 14 paired PC patients and healthy subjects were enrolled for BAs and mucosal microbiota analysis. Cholecystectomy ameliorated DSS-induced murine colitis, accelerated mucosal repair, and induced a significant shifting of fecal microbiota and BAs profiles under colitis status, which featured a higher relative abundance of species involved in BAs metabolism and increased secondary BAs concentrations. Cholecystectomy-associated secondary BAs (LCA, DCA, and HDCA) also ameliorated DSS-induced colitis and accelerated mucosal repair in mice. Cholecystectomy and specific secondary BAs treatments inhibited monocytes/macrophages recruitment in colitis mice. In vitro, cholecystectomy-associated secondary BAs also downregulated monocytes chemokines in the THP-1 derived macrophages through activation of the LXRα-linked signaling pathway. The alterations of mucosal microbiota and fecal BAs profiles were found in the PC patients, characterized as increased species with potential immuno-modulating effects and secondary BAs, which were negatively associated with peripheral monocytes levels. Cholecystectomy-induced secondary bile acids accumulation ameliorated colitis through inhibiting monocyte/macrophage recruitment, which might be mediated by the LXRα-related signaling pathway. Cholecystectomy, after 3 months follow-up, has an immune-regulatory role in murine colitis, preliminarily explaining that no increased risk of IBD had been reported in the PC patients, which still warrants further studies.